2011
DOI: 10.1142/s1088424611003951
|View full text |Cite
|
Sign up to set email alerts
|

Formation and photoinduced properties of zinc porphyrin-SWCNT and zinc phthalocyanine-SWCNT nanohybrids using diameter sorted nanotubes assembled via metal-ligand coordination and π–π stacking

Abstract: Photoinduced electron transfer processes in self-assembled zinc porphyrin (ZnP) or zinc phthalocyanine (ZnPc) with semiconducting (7,6)-and (6,5)-enriched SWCNTs were investigated. To bind photosensitizers to SWCNTs, first, pyrene covalently functionalized with a phenylimidazole (ImPyr) entity was treated with SWCNTs. Exfoliation of SWCNTs occurred due to π−π stacking of pyrene with nanotubes walls leaving the imidazole entity that was subsequently used to coordinate ZnP or ZnPc in o-dichlorobenzene (DCB). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…The study revealed ultrafast energy transfer in the donor-acceptor dyads with time constants on the order of 2 -25 ps depending upon the type of dyad, as shown in Table 1 below. Similar results were obtained when ZnPc and ZnNc were replaced by MgPc and MgNc in DCB [102].…”
Section: Models To Probe Excitation Energy Transfersupporting
confidence: 84%
See 1 more Smart Citation
“…The study revealed ultrafast energy transfer in the donor-acceptor dyads with time constants on the order of 2 -25 ps depending upon the type of dyad, as shown in Table 1 below. Similar results were obtained when ZnPc and ZnNc were replaced by MgPc and MgNc in DCB [102].…”
Section: Models To Probe Excitation Energy Transfersupporting
confidence: 84%
“…The imidazole groups were subsequently used to coordinate ZnP and ZnPc via the metal-ligand axial coordination as shown inFig. 50[135]. In this study, the nanohybrid of SWCNTs(n,m) with Pyr-Im was prepared by stirring SWCNTs andPyr-Im at ambient temperature for 48 hours in DMF as a solvent.…”
mentioning
confidence: 99%
“…Notably, pyrene was used as the linkage in some systems due to the strong π-π interaction between the pyrene and SWCNT [16]. A series of self-assembly zinc porphyrin derivatives noncovalently linked to SWCNT hybrids have been designed by D'Souza and Ito et al [8,[17][18][19][20][21][22], among which the self-assembly mechanisms like the metal-ligand axial coordination, ion pairing, hydrogen bonding and dipole ion pairing have all been reported. As shown in Figure 1a, the self-assembly (TMPyP + )Zn/PyrCOO − /SWCNT and (TPPS − )Zn/PyrNH 3 + /SWCNT hybrids were designed through ion paring [17].…”
Section: Metalloporphyrin/swcnt Hybridsmentioning
confidence: 99%
“…FL quenching is commonly referred to as a useful fingerprint to probe the PET process. As in the case of single-wall carbon tube-zinc porphyrin (SWCNT-ZnP) hybrids (Figure 2A), steadystate and time-resolved FL studies ( Figure 2B) revealed efficient FL quenching of the singletexcited state of zinc porphyrin with the rate constants of charge separation in the range of (3-6) × 10 9 s −1 [90]. In addition, because of increased PET, a uniform film made of CNTs-porphyrin conjugates by simple filtration displayed high light-activated antimicrobial activity toward S. aureus with easy recovery [91].…”
Section: Carbon Materials As Supportsmentioning
confidence: 70%